ADEQUATE EMPIRIC THERAPY OF NOSOCOMIAL FUNGAL INFECTIONS IN ONCOLOGICAL PATIENTS IN THE INTENSIVE CARE UNITS - S. D. Mitrokhin; I. N. Fedankov; A. Zh. Khoteev; A. A. Sokolov (Антибиотики и Химиотерапия)
The results of 3-year experience with voriconasole in oncologic practice are presented. Rational schemes for the use of caspofungin and mycofungin in the treatment of oncologic in patients and the criteria of their use in the thersapy of fungal nosocomial infections were developmed. Good clinical and microbiological efficacy of caspofungin and mycofungin against Candida non-albicans was shown.